2019
DOI: 10.3390/languages4030058
|View full text |Cite
|
Sign up to set email alerts
|

Gender Assignment to Spanish Pseudowords by Monolingual and Basque-Spanish Bilingual Children

Abstract: This study examines gender marking in the Spanish of Basque-Spanish bilingual children. We analyze data collected via a production task designed to elicit 48 DPs, controlling for gender of referents and for number and types of morphological cues to grammatical gender. The goals were to determine the extent to which participants rely on biological cues (female referent =>FEM gender, male referent =>MASC gender) and morpho-phonological cues (-a ending =>FEM, -o ending =>MASC, others =>MASC or FEM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
1
1
0
1
Order By: Relevance
“…Martínez-Nieto (2018) provided evidence for overgeneralization of masculine forms of articles and clitics, as well as a higher accuracy level in masculine forms use in normally developing monolingual Spanish-speaking children and young heritage speakers. A recent study using pseudowords with Spanish monolinguals and Basque-Spanish bilinguals revealed a general preference for masculine gender for both groups (Pérez-Tattam et al, 2019). Similar to Pérez-Pereira (1991a), the authors of this study found that morphophonological cues play a more important role than the biological sex of the referent.…”
Section: Gender Acquisition: Evidence From Typically Developing Spani...supporting
confidence: 54%
“…Martínez-Nieto (2018) provided evidence for overgeneralization of masculine forms of articles and clitics, as well as a higher accuracy level in masculine forms use in normally developing monolingual Spanish-speaking children and young heritage speakers. A recent study using pseudowords with Spanish monolinguals and Basque-Spanish bilinguals revealed a general preference for masculine gender for both groups (Pérez-Tattam et al, 2019). Similar to Pérez-Pereira (1991a), the authors of this study found that morphophonological cues play a more important role than the biological sex of the referent.…”
Section: Gender Acquisition: Evidence From Typically Developing Spani...supporting
confidence: 54%
“…An extensive literature on unilingual Spanish production by L2 bilinguals and heritage Spanish speakers (see Montrul, Foote, & Perpiñán, 2008, a.o. ), and by children with Spanish as L1 and L2 (Pérez-Pereira, 2009;Pérez-Tattam, Ezeizabarrena, Stadthagen-González, & Mueller Gathercole, 2019) also supports the masculine default option. Interestingly, the high variability observed across L1 Spanish speakers in the production and in the acceptance rates of the M/F prenominal modifiers of hermaphroditic Spanish nouns has led some researchers to question the inherent lexical gender feature (Eddington & Hualde, 2008).…”
Section: Gender In Spanish Dpsmentioning
confidence: 81%
“…En términos generales, los resultados hallados en este estudio para los niños con desarrollo típico coinciden con los estudios previos tanto en español como en otras lenguas romances. En concreto, se observa que los niños utilizan el género masculino significativamente mejor que el femenino (Anderson y Lockowitz, 2009;Boloh e Ibernon, 2010;Karmiloff-Smith, 1979;Pérez-Pereira, 1991;Pérez-Tattam et al, 2019).…”
Section: Discussionunclassified